Timing of Prone Positioning During Venovenous Extracorporeal Membrane Oxygenation for Acute Respiratory Distress Syndrome. Issue 1 (9th November 2022) - Giani, Marco; Rezoagli, Emanuele; Guervilly, Christophe; Rilinger, Jonathan; Duburcq, Thibault; Petit, Matthieu; Textoris, Laura; Garcia, Bruno; Wengenmayer, Tobias; Bellani, Giacomo; Grasselli, Giacomo; Pesenti, Antonio; et al.
Abstract : OBJECTIVES: To assess the association of timing to prone positioning (PP) during venovenous extracorporeal membrane oxygenation (V-V ECMO) with the probability of being discharged alive from the ICU at 90 days (primary endpoint) and the improvement of the respiratory system compliance (Cpl, rs). DESIGN: Pooled individual data analysis from five original observational cohort studies. SETTING: European extracorporeal membrane oxygenation (ECMO) centers. PATIENTS: Acute respiratory distress syndrome (ARDS) patients who underwent PP during ECMO. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Time to PP during V-V ECMO was explored both as a continuous and a categorical variable with Cox proportional hazard models. Three hundred patients were included in the analysis. The longer the time to PP during V-V ECMO, the lower the adjusted probability of alive ICU discharge (adjusted hazard ratio [HR] 0.90 for each day increase; 95% CI, 0.87–0.93). Two hundred twenty-three and 77 patients were included in the early PP (≤ 5 d) and late PP (> 5 d) groups, respectively. The cumulative 90-day probability of being discharged alive from the ICU was 61% in the early PP group vs 36% in the late PP group (log-rank test, p <0.001). This benefit was maintained after adjustment for confounders (adjusted HR, 2.52; 95% CI, 1.66–3.81; p <0.001). In the early PP group, PP was associated with a significant improvement of Cpl, rs (4 ± 9 mL/cm H2 O vs 0 ± 12 in the late PP group, p =0.038). CONCLUSIONS: In a large cohort of ARDS patients on ECMO, early PP during ECMO was associated with a higher probability of being discharged alive from the ICU at 90 days and a greater improvement of Cpl, rs.